The Analysis of Human Resources Development in Central Java Province 2009-2013 (Universitas Negeri Semarang, 2015)
This study aims to analyze: (1) the influence of governmentexpenditureon education to HDI in Central Javafrom 2009 to 2013; (2)the influence of government expenditure on health to HDI in Central Java from 2009 to 2013; (3) theinfluence of population density to HDI inCentral Java from 2009 to 2013. Secondary data, from the Central Statistics Agency and Financial Bureau Secretaries of Central Java province in 2009-2013 were used. This study implemented panel data with Fixed Effect Model (FEM)method of Generalized Least Square (GLS). The results show that the governmment expenditure on education and health has positive and significant effect to HDI in Central Java. However, population density doesn’t significantlyaffect the HDI in Central Java.